Motivasi Berprestasi Guru dalam Meningkatkan Kinerja Guru di MA Syaikh Zainuddin NW Anjani - Darsiah Darsiah (MANAZHIM, 2023)
Teacher achievement motivation in improving teacher performance is a spirit to carry out tasks. High teacher achievement motivation in working in a school will have a positive impact on both individuals and organizations or schools, and vice versa. The existence of high achievement motivation can improve the work or performance of teachers, school management, in this context must provide the best way, by paying more attention to teachers so that they can work effectively. High achievement motivation will have great enthusiasm, desire and energy in the individual to work as optimally as possible. High achievement motivation for teachers will have a positive impact on the teaching and learning process in schools and increase teacher competitiveness. This research uses a qualitative approach, the type of case study research with descriptive research method, which is one method that clearly describes the condition of the object of research carried out. The research was conducted by sorting the data and analyzing and interpreting the data that had been collected. Techniques and instruments of data collection using observation, interviews and documentation. The research concludes that motivation as measured by motives, expectations, and incentives is very influential on teacher performance motivation, especially when teachers, who have high morale, are given praise, rewards and rewards, for their best work, by doing their duties as a teacher due to encouragement from motivation, so that it can further improve student learning achievement. To improve the performance of teachers at the MA Sheikh Zainuddin NW Anjani also held MGMP and other similar activities.